2014
DOI: 10.1111/mcn.12112
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of milk whey protein‐based ready‐to‐use therapeutic food in treatment of severe acute malnutrition in Malawian under‐5 children: a randomised, double‐blind, controlled non‐inferiority clinical trial

Abstract: The cost of ready-to-use therapeutic food (RUTF) used in community-based management of acute malnutrition has been a major obstacle to the scale up of this important child survival strategy. The current standard recipe for RUTF [peanut-based RUTF (P-RUTF)] is made from peanut paste, milk powder, oil, sugar, and minerals and vitamins. Milk powder forms about 30% of the ingredients and may represent over half the cost of the final product.The quality of whey protein concentrates 34% (WPC34) is similar to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 50 publications
2
56
1
Order By: Relevance
“…children (10). However, substituting WPC for dry skim milk in a novel RUTF recipe produced recovery rates similar to the standard formulation (42). For children with MAM, a soy/whey RUSF led to a recovery rate similar to that of soy RUSF (4); yet those treated with the soy/whey RUSF were more likely to remain well nourished during a 12-mo follow-up period (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…children (10). However, substituting WPC for dry skim milk in a novel RUTF recipe produced recovery rates similar to the standard formulation (42). For children with MAM, a soy/whey RUSF led to a recovery rate similar to that of soy RUSF (4); yet those treated with the soy/whey RUSF were more likely to remain well nourished during a 12-mo follow-up period (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 24 studies included in this review, only six addressed the issue of relapse and/or reported relapse rates (Bahwere et al, 2014;Ciliberto et al, 2005;Linneman et al, 2007;Querubin, 2006;Taylor, 2002;UNICEF, 2012), and none addressed the relationship between relapse and default or return default. This may be partly attributed to the relatively short duration of most interventions and the fact that most of the studies did not include postintervention follow-up.…”
Section: Relationship Between Recovery and Relapse; Relationship Betwmentioning
confidence: 99%
“…Six of the 24 studies included in this review addressed the issue of relapse and/or reported relapse rates (Bahwere et al, 2014;Ciliberto et al, 2005;Linneman et al, 2007;Querubin, 2006;Taylor, 2002;UNICEF, 2012). Figure 0.1 presents the relapse and default rates reported for each of these studies.…”
Section: What Are the Findings?mentioning
confidence: 99%
See 2 more Smart Citations